Impacts of amino acid supplementation on renal function and nutritional parameters in patients with renal insufficiency: bibliometric analysis and meta-analysis - Liu, Xiaoxia; Li, Qiufu; Zhang, Liyuan; He, Ying; Tan, Sitao; Chen, Xiaoyu; Li, Kefeng (Frontiers in Nutrition, 2025)
ObjectiveThe aim of this study was to summarize the effects of amino acids (AA) on renal function and nutritional indices in patients with renal insufficiency (RI) after treatment and to analyze the development trend in this field.MethodsThe bibliometric evaluation of scholarly contributions in this field was conducted using the Web of Science database, with data analyzed via Bibliometrix and VOSviewer software. The randomized controlled trials (RCTs) published before January 13, 2025, were systematically retrieved from Embase, PubMed, and the Cochrane Library and meta-analyses were performed using Review Manager 5.4 software.ResultsKey areas of focus included oxidative stress, chronic renal failure, hemodialysis, inflammation, chronic kidney disease, risk, plasma, progression, L-arginine, disease, and renal failure. Nine RCTs involving 407 participants were included, AA administration demonstrated significant effects compared to placebo: Increased blood urea nitrogen (MD: 4.21, 95% CI: 1.08 to 7.35, p = 0.008), elevated renal plasma flow (MD: 30.78, 95% CI: 15.36 to 46.21, p < 0.0001), and reduced uric acid levels (MD: −0.47, 95% CI: −0.89 to −0.06, p = 0.02).ConclusionThese findings suggest that AA supplementation may partially improve renal function in RI patients. The progression and possible mechanisms of chronic kidney disease, as well as the search for new biomarkers, will be the trend of research and development in this field.